Perlindungan Hukum Bagi Korban Kekerasan Seksual Terhadap Anak-Anak di Bawah Umur dalam Lingkungan Keluarga - Pryanka Ceza Oktrian; Safina Elfitra Rahmah; Rizky Nazela Shaqina; Schevilya Arda Mugharta; Hikmah Ayudiah Putri; Dewi Zakiatun Nufus; Sarah Laksana Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Children are the next generation of the nation and will inherit the cultures and customs that are in their environment, especially the family environment. Child Protection is an effort to protect children's human rights so that they can continue to grow and develop into the hope and successor of the nation and state. The family is formed on a sense of security, comfort and affection, unfortunately there are some children who get insecurity and coercion within the scope of their family. The method used in this research is a normative juridical approach, namely by conducting research based on legal materials or references by examining the theories and concepts of these legal materials relating to the legal principles of legislation related to this writing or research. This research aims to examine in depth the legal protection for victims of sexual violence against minors in the family environment, as well as identify problems and obstacles in the application of the Law in order to strengthen legal protection for victims. The results showed that the existing law is still weak with the lack of human resources equipped with special training in handling cases like this.